Development and Implementation of a Pharmacist‐Led Aspirin Deprescribing Algorithm in Older Adults - Sano, Ugene; Uricchio, Marissa; Redling, Theresa; Zeffren, Noam; Bente, Jessica (Journal of the American Geriatrics Society (JAGS), 2025)
ABSTRACT Background Recent literature has demonstrated that low‐dose aspirin for primary prevention of atherosclerotic cardiovascular disease (ASCVD) in older adults has been associated with a higher incidence of bleeding events without additional benefit compared to standard prevention strategies. This study evaluated the impact of an aspirin deprescribing algorithm on inappropriate aspirin use in patients older than 70 years across two primary care offices. Methods This institutional review board‐approved, pre‐ and post‐interventional study included patients 70 years and older on low‐dose aspirin with office visits scheduled from April 1, 2023–March 30, 2024. An aspirin deprescribing algorithm was developed by an interdisciplinary team to guide prescribers with deprescribing. The pharmacist screened patients eligible for deprescribing via chart review of visits from April 2023–October 2023. Patients eligible for deprescribing in the pre‐implementation phase were included as the interventional group of the post‐implementation phase (November 2023–March 2024). Follow‐up was 5 months total. The primary endpoint was incidence of inappropriate aspirin use, defined as patients taking aspirin without documented diagnosis of ASCVD in patients’ electronic health record. A subgroup analysis was performed on patients who were eligible for deprescribing and monitored safety endpoints such as incidence of major and minor bleeds based on the International Society on Thrombosis and Hemostasis criteria, major cardiovascular events, and cardiovascular‐related hospitalizations. Duration of follow‐up for secondary endpoints was 5 months during the post‐implementation period. Results Four‐seventy four patients were included. The incidence of inappropriate aspirin use in the pre‐implementation group was 24.9% and 118 patients were eligible for deprescribing. For the post‐implementation group, 22 patients had aspirin deprescribed, resulting in 20.3% inappropriate aspirin use (p < 0.01). In the subgroup analysis, no difference of major and minor bleeds, major cardiovascular events, and cardiovascular‐related hospitalizations were observed. Conclusion A deprescribing algorithm was associated with a statistically significant reduction in inappropriate aspirin use in older adults for the indication of primary ASCVD prevention. Algorithm‐based deprescribing can reduce bleeding risk and polypharmacy in older adults.